The Relevance Between Values of Akhlak Education in Adnan and Syahid's Tafsir with Education Law in Indonesia - Moh Abdul Kholiq Hasan; Khusnul Arifah Ma’sum (Islamic Religious Education Departement, 2024)
This research examines the relevance between the values of akhlak education In Adnan and Syahid's Tafsir with education law in Indonesia, the perspective of the surah Luqman. The research uses content analysis methods with hermeneutic approaches and comparative methods. The results show that the value of ethical education in interpreting the al-Qur'an Suci Basa Jawi and the Tafsir Al-Huda in principle is similar. Both broadly transmit Javanese noble values, which include: (1) Tawheed, (2) Filial piety to both parents, (3) Gratitude, (4) Patience, (5) Wisdom, (6) Simplicity, (7) Sincerity, and (8) the value of honesty. The relevance of the values of akhlak education above with the Indonesian education law emerges in attitudes and actions (1) Religion, (2) Discipline, (3) Independence and Responsibility, (4) Honesty, and (5) Concern for the social and natural environment. From an early age, make them habits when they are adults.